2022
DOI: 10.3332/ecancer.2022.1451
|View full text |Cite
|
Sign up to set email alerts
|

A single-arm feasibility phase II study of EMF (erlotinib + methotrexate + 5-fluorouracil) regimen in platinum-refractory recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC)

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is a huge burden in India with the majority of patients presenting in advanced unresectable stages. Innovative, low-cost but efficacious regimens that can be easily administered in the outpatient setting are the need of the hour. We envisaged assessing whether a readily available triplet therapy of erlotinib + methotrexate + 5-fluorouracil (EMF) is efficacious in terms of extending life and maintaining the quality of life in such patients. Patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Our study reports CTC as a biomarker in recurrent/metastatic HNSCC, which is a difficult scenario but an unmet need. The detailed characteristics of the patients recruited have been elaborated in our previous study [ 16 ]. The CTCs clearance at 3 months of palliative chemotherapy (EMF: erlotinib + methotrexate + 5-Flourouracil) has been associated with a better PFS (6 months versus 4 months) and OS (10 months versus 8 months) numerically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study reports CTC as a biomarker in recurrent/metastatic HNSCC, which is a difficult scenario but an unmet need. The detailed characteristics of the patients recruited have been elaborated in our previous study [ 16 ]. The CTCs clearance at 3 months of palliative chemotherapy (EMF: erlotinib + methotrexate + 5-Flourouracil) has been associated with a better PFS (6 months versus 4 months) and OS (10 months versus 8 months) numerically.…”
Section: Discussionmentioning
confidence: 99%
“…Response assessment was done at 3 monthly intervals using contrast-enhanced computed tomography (CECT)-face/neck/chest and response was evaluated using RECIST 1.1. The primary objective was to assess the objective response rates of the regimen, which has been reported previously by our group [ 16 ]. Here we report the secondary objective of the study that was to assess the role of CTCs as a surveillance biomarker for disease recurrence and metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…Some small molecular inhibitors of EGFR are also under investigation for the management of HNSCC, including selective inhibitors (e.g., gefitinib, erlotinib) ( 80 , 81 , 105 , 106 ) and dual-target inhibitors (e.g., afatinib, lapatinib, and dacomitinib) ( 82 , 107 ).…”
Section: Hnc Molecular Pathogenesismentioning
confidence: 99%
“…Thus, size-based approaches that exploit the bigger CTCs with respect to haematogenous cells for their isolation might miss the isolation of small-sized CTCs ( 8 ), which we have documented in our previous study on oral squamous cell carcinoma (OSCC) patients ( 9 ). Studies have shown the prognostic role of CTCs in head and neck squamous cell carcinoma (HNSCC) including OSCC ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%